Meningkatkan Partisipasi Remaja Islam Masjid (RISMA) Al-Muttaqin Terhadap Kegiatan Keagamaan Di Dusun Ii Pondok Kubang - Chotima, Indah Husnil; Ismil, Aulia; Fitra, Deva Amalia; Agriani, Salwa Eka; Salsabilla, Sakinah Aulya; Rambe, Novia Ratna Sari; Shintia, Shintia; Adillah, Dzakiyah; Erdiansyah, M. Alif; Akbar, M. Riski; Ishfahandi, Adib Rovi (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Real Work Lecture (KKN) is a program that involves students to actively participate in problems faced by the community. In addition, KKN functions as a means to showcase student initiatives in lectures with their applications in the community. Mosque-Based KKN is one type of KKN offered by Fatmawati Soekarno Bengkulu. Mosque-based KKN is carried out in a mosque-based area with the aim of increasing mosque activities to support the spread of the Islamic Message and mobilizing the community in development through various activities that can involve, include, and grow the community. The purpose of this study is to find and increase participation. The result of this activity is to reactivate the Islamic Youth Mosque (RISMA) of the Al-Muttaqin Mosque in Dusun II, Pondok Kubang Village, which was previously vacant with the election of a new administrator. The active RISMA Al-Muttaqin Mosque participated in collaborating with KKN students while serving in Pondok Kubang Village.